Potensi Antioksidan Kombinasi Ekstrak Jahe Merah (Zingiber officinale var Rubrum) dan Bunga Telang (Clitoria ternatea L) dengan Metode DPPH: Antioxidant Potential of Combination of Red Ginger Extract (Zingiber officinale var Rubrum) and Butterfly Pea Flower (Clitoria ternatea L) using the DPPH Method - Della Jauharotus Sa’adah; Rissa Laila Vifta; Windi Susmayanti (Journal of Holistics and Health Sciences (JHHS), 2023)
The combination of two or more natural product was thought to increase their pharmacological activity as an antioxidant. Red ginger and blue butterfly pea flowers are two natural product that can be combined to have better antioxidant activity. The aim of this research was to analyze the antioxidant activity of the combination of red ginger extract (JM) and butterfly pea flower (TL) based on the IC50 value. Red ginger and butterfly pea flowers was used as the sample. Extraction was carried out by maceration method using 96% ethanol as solvent and n-hexane as purification solvent. The determination of antioxidant activity have done by using the DPPH method. The IC50 value were analyzed statistically using the One Way Anova test and the LSD test. The yield of purified red ginger n-hexane extract was 63.3% and 90.4% of butterfly pea flower. Both of red ginger and butterfly pea flower extracts were positive for flavonoids, tannins, saponins, and alkaloids. The IC50 value of JM:TL (0:1) combination was 31.17 ppm, JM:TL (1:0) combination was 65.644 ppm, JM:TL (1:1) combination was 38.65 ppm, JM:TL (1:2) ombination was 54.775 ppm, and JM:TL (2:1) combination was 22.262 ppm. The combination of red ginger extract and butterfly pea flower extract have a strong to very strong category of antioidant activity. The LSD analyzed results showed that there is a significant difference in the IC50 value in all combinations with a p-value <0.05. ABSTRAK Kombinasi dua atau lebih bahan alam diduga dapat meningkatkan aktivitas farmakologisnya sebagai antioksidan. Rimpang jahe merah dan bunga telang merupakan dua bahan alam yang dapat dikombinasikan dan diduga berpotensi memiliki aktivitas antioksidan yang baik. Tujuan penelitian untuk menganalisis aktivitas antioksidan kombinasi ekstrak jahe merah (JM) dan bunga telang (TL) berdasarkan nilai IC50. Penelitian dilakukan secara eksperimental dengan sampel jahe merah dan bunga telang. Ekstraksi dilakukan dengan metode maserasi menggunakan pelarut etanol 96% dan purifikasi ekstrak menggunakan pelarut n-heksan. Pengujian aktivitas antioksidan menggunakan metode DPPH. Data dianalisis secara statistika menggunakan uji One Way Anova dan uji LSD. Rendemen ekstrak purifikasi n-heksan jahe merah 63,3% dan bunga telang 90,4%. Hasil pengujian metabolit sekunder pada kedua ekstrak positif mengandung flavonoid, tanin, saponin, dan alkaloid. Nilai IC50 Kombinasi JM:TL (0:1) 31,17 ppm, Kombinasi JM:TL (1:0) 65,644 ppm, Kombinasi JM:TL (1:1) 38,651 ppm, Kombinasi JM:TL (1:2) 54,775 ppm, dan Kombinasi JM:TL (2:1) 22,262 ppm. Aktivitas antioksidan kombinasi ekstrak jahe merah dan ekstrak bunga telang menghasilkan nilai IC50 dengan kategori kuat sampai dengan sangat kuat Hasil uji LSD menunjukkan adanya perbedaan signifikan pada nilai IC50 pada seluruh kombinasi dengan p-value <0,05.